Safety of EstroG‐100™ as a novel food pursuant to Regulation (EC) No 258/97. (24th October 2016) - ,; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen Ildico; Mangelsdorf, Inge; McArdle, Harry; Naska, Androniki; Neuhäuser‐Berthold, Monika; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on EstroG‐100 ™ as a novel food (NF) submitted pursuant to Regulation (EC) No 258/97 of the European Parliament and of the Council. The NF is EstroG‐100 ™, a hot‐water extract of a mixture of three herbal roots ( Cynanchum wilfordii Hemsley, Phlomis umbrosa Turcz. and Angelica gigas Nakai ), which is concentrated and spray‐dried. The information provided on the composition, specifications and stability of the NF is sufficient, and does not raise safety concerns. The applicant intends to use EstroG‐100 ™ in food supplements, with a proposed maximum intake level of 514 mg/day. The target population is post‐menopausal women. The Panel considers that the information provided does not raise safety concerns as regards the genotoxicity of the NF. The Panel considers that the no‐observed‐adverse effect level (NOAEL) derived from the subchronic 90‐day oral toxicity study with EstroG‐100 ™, which was supported by observations in other studies, is 500 mg/kg body weight (bw) per day. Taking into account the NOAEL and the proposed maximum intake level, the Panel considers that the margin of safety of 68 is not sufficient. Based on the absence of chronic toxicity data, increase in effects with exposure duration in toxicity studies, and the absence of investigations of liver parameters and haematology in human studies, the Panel applies the uncertainty factor of 200 to derive the maximum safe intake level for the NF. Thus, the Panel concludes that the NF, EstroG‐100 ™, is safe for the use in food supplements at the maximum intake level of 175 mg/day for an adult of 70 kg bw.